Factors affecting participation decision and amount of physical activity among urban dwellers in Malaysia - Cheah, Yong Kang; Azahadi, Mohd; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (Elsevier, 2017)
Objectives: The rapid rise in the prevalence of physical inactivity-related diseases has become a serious public health issue worldwide. The objective of the present study is to examine the factors affecting participation in physical activity among urban dwellers in Malaysia. Study design: This cross-sectional study measures physical activity using a rigorous regression model. Methods: Data are obtained from the National Health and Morbidity Survey 2011 (NHMS 2011). A lognormal hurdle model is used to analyse the participation decision and the amount decision of physical activity. Results: The results show that income, gender, ethnicity, marital status and employment status are significantly associated with participation decision and amount decision. However, age, insurance and self-rated health only affect participation decision, whereas family size, education and smoking only affect amount decision. Conclusions: It can, thus, be concluded that sociodemographic, insurance, lifestyle and health factors play an important role in determining physical activity behaviour among urban dwellers. When formulating policies, special attention must be paid to these factors.